Update on systemic treatment for newly diagnosed inflammatory breast cancer - Chainitikun, Sudpreeda (J Adv Res, 2020)
BACKGROUND: Inflammatory breast cancer (IBC) is a rare and aggressive disease, accounting for 2–4% of new cases of breast cancer. Owing to its aggressive nature, IBC represent approximately 8–10% of breast cancer deaths. Management of IBC requires a multidisciplinary team for decision-making involving a composite of systemic treatment, surgery, and radiation, or “Trimodality Treatment.” Because of the rarity of the disease, systemic therapy of IBC traditionally has been extrapolated from non-IBC clinical trials. AIM OF REVIEW: The purpose of this review is to provide an overview of the development of systemic treatment of IBC from the past to the present by focusing on IBC clinical trials, including chemotherapy and targeted therapies. KEY SCIENTIFIC CONCEPTS OF REVIEW: We discuss their effects on pathologic complete response (pCR) and survival outcomes, the predictive markers, and the adverse events of these therapies. Further, we summarized the current standard treatment stratified by molecular subtypes based on clinical data. Finally, we discuss the future trend of systemic therapy, including immunotherapy and ongoing IBC clinical trials.